The Role of Philosophy of Science in Creating a Profile of Pancasila Students in Indonesia - Yayu Setia Hartati; Sustin Komariyah; Susan Susyanah (Publikasi Indonesia, 2024)
This research aims to identify the role of philosophy of science in implementing the Pancasila student profile in Indonesia. This research uses a qualitative method approach with a library study design. The results of this research conclude that in realizing the Pancasila student profile in the curriculum, which is a plan and structure that includes objectives, content, materials and teaching methods that must be highlighted, it can have a good impact on the implementation of Pancasila values, focusing on the role of the philosophy of science as a strengthening of the inner self. students. In applying and implementing Pancasila values into the learning process. The philosophy of science is something that opposes negative things as a threat to disintegrate a society. Philosophy also for students can be one of the things that oppose the danger that causes separation because students have well explored the noble values of Pancasila that are art.